PUBLIC SECTOR INNOVATION ON COVID-19 IN SOUTH SUMATRA: CALLING FOR A MORE SUSTAINABLE INNOVATION - Sena Putra Prabujaya; Anang Dwi Santoso (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
On the one hand the COVID-19 pandemic is seen as a disaster that has had a massive impact on various aspects of life, but on the other hand it is considered as momentum to urge the public organizations to be more innovative and adaptive in adapting to various types of new conditions and adjustments. Many studies have explored public sector innovation, especially in normal circumstances. While studies on the public sector innovation in a critical situation have not caught much attention from academics. This study aimed to fill the gap by analyzing the public sector innovation in South Sumatra as one of the provinces with the highest number of COVID-19 cases in Indonesia. There was a total of 16 innovations in this study. Content analysis was conducted to determine the types, categories, innovators, and challenges faced. The researchers found that the organizations that innovate (innovators) consisted of city governments, regency governments, provincial governments, central government representatives, and the community. Meanwhile, for the innovation category, the researchers found more innovations with types of public services and health information. The researchers also found three types of innovation categories in South Sumatra including mass/social resilience, quick response/quick wins, and public knowledge. Lastly, the challenges in implementing the innovation which includes public awareness, human resources, financial, facilities and infrastructure, and time. Academically, this study contributes to the understanding of public sector innovation in a critical situation, that innovation in such condition is an innovation that was made for pragmatic purposes and it won’t last. It is only adjusted to the situations that force people to implement physical distancing to each other.